Maximizing Plastic Surgery Education Impact: Lessons from Resident Learning Styles and Experiential Learning Theory. Issue 7 (July 2019) - Saldanha, Francesca Y. L.; Levites, Heather A.; Staffa, Steven J.; Roussin, Christopher; Allori, Alexander C.; Rogers-Vizena, Carolyn R.
Abstract : Background: Residents in many surgical disciplines express a strong preference for hands-on learning, but no studies have focused on plastic surgery. This initial study aims to ascertain the learning styles of plastic surgery residents, and identify potential trends that may better guide curriculum development. Methods: Kolb Learning Style Index v. 3.1 was administered to plastic surgery residents across all training levels at three residency programs. The Kolb Learning Style Index is a 12-item questionnaire that characterizes an individual's learning style into 1 of 4 major categories: converging; accommodating; assimilating; and diverging. Results: The surveyed cohort of plastic surgery residents (n = 45) demonstrated a diverse mix of learning styles: converging (38%, n = 17); accommodating (24%, n = 11); diverging (20%, n = 9); and assimilating (16%, n = 7). One resident was balanced between converging and accommodating (2%, n = 1). Despite varied learning styles, the majority (64%, n = 29) demonstrated a preference for "active experimentation, " for example, hands-on learning. Conclusions: A preliminary assessment of learning styles among plastic surgery residents suggests that they have mixed learning styles. This contrasts with the existing literature from other surgical specialties where a single learning style dominates. However, like these other specialties, active experimentation is particularly valued. As such, it behooves the plastic surgery educator to continue to strive for balance between book learning and hands-on experience for residents at all levels of training, to engage residents with all learning styles.